Preliminary Investigation of a Questionnaire, Based On the Model of Stages and Processes of Change towards Exercise - Physical Activity - Papaioannou, Αθανάσιος; Bebetsos, Ευάγγελος; Kafetzi, Σουλτάνα; Sagovitch, Αλέξανδρος (Inquiries in Physical Education and Sport, 2005)
The study was based on the model of stages, where people according to the strategies/procedures that they adopt towards exercise, are classified on the preconteplation, contemplation, preparation, action and maintenance stages of exercise. The aim of this study was the preliminary investigation of the validity of the exercise stages of change questionnaire. The sample consisted of 482 physical education students. Although the results of the exploratory factor analysis supported the factorial validity of the questionnaire, further improvement is needed. As it was shown, the procedures assorted the sample to the stages of change according to the theory, but only half of these procedures contributed to this classification. Students, who exercised regularly, had higher scores than the students who exercised less or not at all, in all changes’ procedures. The results are supportive not only on the validity of this instrument, but also on the implication of the model on the enhancement of exercise and physical activity in Greece.